2020
DOI: 10.3390/ma13051168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recycled Iron Powder as Fine Aggregate on the Mechanical, Durability, and High Temperature Behavior of Mortars

Abstract: This study evaluates the mechanical, durability, and residual compressive strength (after being exposed to 20, 120, 250, 400 and 600 °C) of mortar that uses recycled iron powder (RIP) as a fine aggregate. Within this context, mechanical strength, shrinkage, durability, and residual strength tests were performed on mortar made with seven different percentages (0%, 5%, 10%, 15%, 20%, 30% and 50%) of replacement of natural sand (NS) by RIP. It was found that the mechanical strength of mortar increased when replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…These higher thermal cracks of the mortar made with WSS and WCB should be one of the main reasons for the lower strength than NS. This behavior is in agreement with the literature [ 22 , 32 , 36 ]. It was shown that a significantly higher permeability occurred when heated at a higher temperature (e.g., 300 °C) for the mix made with coarser particles (size of aggregate is around 5 mm) than the mix containing a small-sized aggregate of 0.6 mm [ 19 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These higher thermal cracks of the mortar made with WSS and WCB should be one of the main reasons for the lower strength than NS. This behavior is in agreement with the literature [ 22 , 32 , 36 ]. It was shown that a significantly higher permeability occurred when heated at a higher temperature (e.g., 300 °C) for the mix made with coarser particles (size of aggregate is around 5 mm) than the mix containing a small-sized aggregate of 0.6 mm [ 19 ].…”
Section: Resultssupporting
confidence: 93%
“…Conversely, the particle shape of NS was uncrushed, smooth in surface and nearly well-rounded ( Figure 1 a,d), which provided a weak bond among the particles and weak ITZ between NS and cement paste, leading to lower tensile and flexural strength. Similar results were reported in the literature [ 32 ]. It is noted that a significantly higher amount of very fine particles (smaller than 74 µm) of WSS (12.38%) and WCB (21.41%) was found on the pan of the ASTM sieve.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The decrease of water absorption with time referred to a modification of total void space in concrete. In a related study, Miah et al [31] observed a similar trend using waste iron as fine aggregate. They reported that the water absorption decreased with the increasing the ratio of iron waste.…”
Section: Water Absorptionmentioning
confidence: 61%